Inside Front Cover, Volume 1, Number 1, July 2022. Issue 1 (29th July 2022) - Junaid, Muhammad; Nurmi, Heikki A.; Latikka, Mika; Vuckovac, Maja; Ras, Robin H. A.
Abstract : Inside Front Cover : The cover image is based on the Research Article Oscillating droplet tribometer for sensitive and reliable wetting characterization of superhydrophobic surfaces by Junaid et al.